ARTI DAN RAGAM GAYA BAHASA DALAM TERJEMAHAN SURAH ALBAQARAH - Hidayah, Dimas Nurul; Heryana, Nanang; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by the desire to understand the style of language and the meaning of the style of language in the translation of the chapter of Albaqarah. The general problem studied is the style of language in the surah. The subproblem is how language styles and stylistic meanings are in Albaqarah surah. This research uses a descriptive method with qualitative form. Data collection techniques used documentary study techniques. The data collection tool is the researcher himself as the main instrument or instrument. The data source is Albaqarah surah in Qur'an Ministry of Religious Affairs of Indonesia in 2010 and this research data in the form of words, phrases, sentences, and verses in the form of language style. Based on data analysis, this study yields a conclusion that comparative language style contained in chapters Albaqarah amounted to 17 pieces, language of contradictions to 26 pieces, language style of the links 4, and language style of the iteration is not contained in the Albaqarah surah. Keywords: Albaqarah, Language, Qur’an,Style of Language